2003
DOI: 10.1017/s0022029903006216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stimulation intensity on oxytocin release before, during and after machine milking

Abstract: Release of oxytocin (OT) is essential for milk ejection in dairy cows (Lefcourt & Akers, 1983; Bruckmaier & Blum, 1998). During milk ejection, alveolar milk is shifted into the cistern, which causes an increase of intracisternal pressure (Bruckmaier et al. 1994). To initiate maximum milk ejection at the start of milking, increasing OT concentration beyond a threshold level is sufficient (Schams et al. 1983). Increasing OT concentration beyond this threshold has no additional effect on intracisternal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 2 publications
3
28
0
2
Order By: Relevance
“…in Gir cows, as previously described in Holstein (Gorewit et al, 1992;Bar-Peled et al, 1995), Brown Swiss (Tancin et al, 1995), and Brown Swiss × German Braunvieh cows (Weiss et al, 2003), all of which are considered to be well adapted to milking when compared with Gir cows. Other investigators have also demonstrated that udder stimulation induces oxytocin release in Shami cows (Kaskous et al, 2006) and Murrah buffaloes (Thomas et al, 2005).…”
Section: Oxytocin Release During Exclusive Suckling or Hand-and Machimentioning
confidence: 99%
“…in Gir cows, as previously described in Holstein (Gorewit et al, 1992;Bar-Peled et al, 1995), Brown Swiss (Tancin et al, 1995), and Brown Swiss × German Braunvieh cows (Weiss et al, 2003), all of which are considered to be well adapted to milking when compared with Gir cows. Other investigators have also demonstrated that udder stimulation induces oxytocin release in Shami cows (Kaskous et al, 2006) and Murrah buffaloes (Thomas et al, 2005).…”
Section: Oxytocin Release During Exclusive Suckling or Hand-and Machimentioning
confidence: 99%
“…Because of this property, oxytocin is often injected into cattle that are under stress or unable to produce much milk to enhance milk production 31 . However, some research indicates that administering oxytocin to stimulate uterine contractions in pregnant cows can lead to increased early embryonic death 32 . The present results indicate that oxytocin does not affect the activity of serum PON1 as it showed a very high IC 50 of 507.72 mg/mL (Table 1 and Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, oxytocin release may be influenced by the type of stimulus (e.g., the suction exerted by the calf or milking) (MARNET; NEGRÃO, 2000; . This stimulus interferes with the ejection of alveolar milk and milk production (MARNET; NEGRÃO, 2000;WEISS;DZIDIC;BRUCKMAIER, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In ewes, the mother takes exclusive care of her own lamb (LÉVY et al, 1995). The release of oxytocin can be influenced by the type of stimulus (i.e., the suction exerted by the calf or milking, which can interfere with the milk ejection fraction and its production) (MARNET; LABUSSIERE, 1998;WEISS;DZIDIC;BRUCKMAIER, 2003).…”
Section: Introductionmentioning
confidence: 99%